2017 IEEE Cybersecurity Development (SecDev) 2017
DOI: 10.1109/secdev.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Developers Need Support, Too: A Survey of Security Advice for Software Developers

Abstract: Abstract-Increasingly developers are becoming aware of the importance of software security, as frequent high-profile security incidents emphasize the need for secure code. Faced with this new problem, most developers will use their normal approach: web search. But are the resulting web resources useful and effective at promoting security in practice? Recent research has identified security problems arising from Q&A resources that help with specific secure-programming problems, but the web also contains many ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 9 publications
0
78
0
Order By: Relevance
“…The study reported here joins recent calls to understand more about how developers use guidance found on-line [3] and to identify methods for studying developers' security behavior [1]. We hypothesize that social factors are effective in motivating developers to write secure code and postulate that these factors will be evident within interactions undertaken between developers communicating in an on-line community setting.…”
mentioning
confidence: 82%
“…The study reported here joins recent calls to understand more about how developers use guidance found on-line [3] and to identify methods for studying developers' security behavior [1]. We hypothesize that social factors are effective in motivating developers to write secure code and postulate that these factors will be evident within interactions undertaken between developers communicating in an on-line community setting.…”
mentioning
confidence: 82%
“…One possible strategy to mitigate security smells is to develop concrete guidelines on how to write IaC scripts in a secure manner. When constructing guidelines, the IaC community can take the findings of Acar et al [54] into account, and include easy to understand, task-specific examples on how to write IaC scripts in a secure manner.…”
Section: Use Of Http Without Tlsmentioning
confidence: 99%
“…One problem is that developers rarely need to use security techniques such as cryptography in their software, and when they do, the APIs are difficult to use [16]. Guidance in online sources used by developers is not comprehensive or robust [17], and often not correct [18]. Activities designed to raise awareness are perceived by developers to be helpful, but may not have lasting impact on teams [19].…”
Section: Introductionmentioning
confidence: 99%